Comparative Genomics Assisted Functional Characterization of Rahnella aceris ZF458 as a Novel Plant Growth Promoting Rhizobacterium - Xu, Shuai; Zhao, Yurong; Peng, Yue; Shi, Yanxia; Xie, Xuewen; Chai, Ali; Li, Baoju; Li, Lei (Frontiers in Microbiology, 2022)
Many Rahnella strains have been widely described as plant growth-promoting rhizobacteria with the potential to benefit plant growth and protect plants from pathogens. R. aceris ZF458 is a beneficial plant bacterium isolated from swamp soil with the potential for biocontrol. Strain ZF458 has shown broad-spectrum antagonistic activities against a variety of plant pathogens and exhibited a dramatic effect on controlling Agrobacterium tumefaciens in sunflowers. The R. aceris ZF458 genome sequence contained a 4,861,340-bp circular chromosome and two plasmids, with an average G + C content of 52.20%. Phylogenetic analysis demonstrated that R. aceris ZF458 was closely related to R. aceris SAP-19. Genome annotation and comparative genomics identified the conservation and specificity of large numbers of genes associated with nitrogen fixation, plant growth hormone production, organic acid biosynthesis and pyrroloquinoline quinone production that specific to benefiting plants in strain ZF458. In addition, numerous conserved genes associated with environmental adaption, including the bacterial secretion system, selenium metabolism, two-component system, flagella biosynthesis, chemotaxis, and acid resistance, were also identified in the ZF458 genome. Overall, this was the first study to systematically analyze the genes linked with plant growth promotion and environmental adaption in R. aceris. The aim of this study was to derive genomic information that would provide an in-depth insight of the mechanisms of plant growth-promoting rhizobacteria, and could be further exploited to improve the application of R. aceris ZF458 in the agriculture field.